2017
DOI: 10.1017/s0272263117000146
|View full text |Cite
|
Sign up to set email alerts
|

Semantic and Structural Tasks for the Mapping Component of L2 Vocabulary Learning

Abstract: The type of processing–resource allocation (TOPRA) model predicts that increasing one type of processing (semantic, structural, or mapping oriented) can decrease other types of processing and their learning counterparts. This study examined how semantic and structural tasks affect the mapping component of second language (L2) vocabulary learning. Japanese-speaking L2 English learners attempted to map secondary meanings of 24 English homographs. Each participant studied them (a) while making pleasantness rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…To explore proficiency reporting practices for different types of learners and learning contexts, we coded studies according to whether the study reported on learning in a second language context, a foreign language context, or a heritage language context, or whether the study reported on more than one type of learner or learning context. We distinguished between the different kinds of context as follows: Second language context: an environment in which the target language is spoken/used in the larger community, as in LaScotte and Tarone's (2019) study involving adult learners of English as a second language from various first language backgrounds enrolled in an intensive English program in the United States. Foreign language context: an environment in which the target language is not the dominant language of the larger community, exemplified by Kida and Barcroft's (2018) study of Japanese‐speaking learners of English studying at a university in Japan. Heritage language context: a context in which learners have a familial connection to the target language and often learned or were exposed to that language during childhood, as in Benmamoun and Albirini's (2018) study involving learners of Arabic of Arab descent, and with early exposure to Arabic, living in the United States. …”
Section: Resultsmentioning
confidence: 99%
“…To explore proficiency reporting practices for different types of learners and learning contexts, we coded studies according to whether the study reported on learning in a second language context, a foreign language context, or a heritage language context, or whether the study reported on more than one type of learner or learning context. We distinguished between the different kinds of context as follows: Second language context: an environment in which the target language is spoken/used in the larger community, as in LaScotte and Tarone's (2019) study involving adult learners of English as a second language from various first language backgrounds enrolled in an intensive English program in the United States. Foreign language context: an environment in which the target language is not the dominant language of the larger community, exemplified by Kida and Barcroft's (2018) study of Japanese‐speaking learners of English studying at a university in Japan. Heritage language context: a context in which learners have a familial connection to the target language and often learned or were exposed to that language during childhood, as in Benmamoun and Albirini's (2018) study involving learners of Arabic of Arab descent, and with early exposure to Arabic, living in the United States. …”
Section: Resultsmentioning
confidence: 99%
“…There have been several discussions of theories of L2 vocabulary learning (e.g., Barcroft, 2015; Dóczi & Kormos, 2016; Hulstijn, 2001; Kormos, 2020; Laufer, 2020; Moonen, De Graaff, & Westhoff, 2006; Nation, 2013; Nation & Webb, 2011; see also Suzuki, Nakata, & DeKeyser, 2019, for a recent discussion of desirable difficulty; and Lightbown, 2008, on transfer appropriate processing). However, (quasi‐)empirical studies aiming to directly contribute to theory building are relatively scarce, with the majority of these studies focusing on the ILH (but see also Barcroft, 2002, 2003, 2004, 2009, 2019; Kida & Barcroft, 2018, testing the type of processing–resource allocation, or TOPRA, model). The large number of studies investigating the ILH may be due to its strengths of (a) proposing a clear, falsifiable hypothesis; (b) demonstrating how the hypothesis can be tested (Hulstijn & Laufer, 2001); and (c) aiming to provide transparent pedagogical suggestions—the findings of the ILH studies provide pedagogical implications that can easily be applied to vocabulary teaching.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, EFL students studied 24 English homographs (a) while making pleasantness ratings about word meaning (mapping plus semantic processing); (b) while counting letters in each word (mapping plus structural processing); and (c) without any additional task (mapping only). Results of L1 and L2 free recalls and L2-to-L1 and L1-to-L2 cued recalls indicated higher free recall in the semantic condition than the structural condition and a higher cued recall in the mapping condition than the semantic and structural conditions (Kida & Barcroft, 2018).…”
Section: Introductionmentioning
confidence: 78%